Global trends in childhood urinary tract infections, 1990–2021: results from the GBD study - Zuo, Xiepeng; Fang, Cheng; Wang, Chuanming; Fang, Ziqi; Liang, Qingyuan; Dai, Zhaodelong; Sun, Meng; Liu, Liwei; Wen, Simeng (Frontiers in Public Health, 2025)
BackgroundUrinary tract infections (UTIs) represent a prevalent urological disorder in childhood populations with substantial clinical implications. This study reports global trends from 1990 to 2021 in incident cases, incidence rates, mortality counts, mortality rates, disability-adjusted life years (DALYs), and DALY rates attributable to childhood UTIs.MethodsUtilizing Global Burden of Disease (GBD) 2021 data, we analyzed incidence, mortality, and DALY rates (per 100,000 population) with 95% uncertainty intervals (UI) for children aged 0–14 years. Data spanned 204 countries and territories, stratified by age, sex, and geographic location. Temporal trends were quantified using: Segmented regression to compute Annual Percentage Change and Average Annual Percentage Change. Log-linear regression models to derive Estimated Annual Percentage Change with 95% confidence intervals (CI). Associations between disease burden indicators and the Socio-demographic Index (SDI) were characterized using generalized additive models (GAMs) to capture potential nonlinear relationships.ResultsFrom 1990 to 2021, global incident cases of childhood UTIs increased by 10.31% (95% UI: 4.33–13.82), whereas the global incidence rate decreased by 4.65% (95% UI: −9.82 to −1.60). Concurrently, downward trends were observed in deaths, DALYs, mortality rates, and DALY rates. Notably, childhood UTIs burden demonstrated significant associations with regional socioeconomic development and environmental conditions. In low-SDI regions, incident cases surged by 63.43% (95% UI: 47.21–76.20). This starkly contrasts with the declines observed in high-middle and high-SDI regions. These findings underscore the elevated UTIs incidence rates in tropical countries, necessitating targeted resource allocation for prevention and clinical management.ConclusionFrom 1990 to 2021, the global incidence rate of childhood UTIs exhibited a downward trend. However, this trend reversed over the past decade, with a marked increase in incidence rates. Significant disparities in incidence rates were observed across population groups globally, stratified by sex, age, geographical location, and socioeconomic status. The incidence rate of UTIs is higher among children in socioeconomically disadvantaged and tropical regions. A representative example is the sustained increase in UTIs incidence among children in South Asia. Conversely, incidence rates were higher in girls, while mortality and DALYs were significantly elevated in boys. To optimize resource allocation and ensure essential treatment reaches those in need, governments and health organizations must tailor interventions based on regional and population-specific burdens. These findings underscore the necessity of developing effective, tailored prevention and treatment strategies.